Five year follow up of laser in situ keratomileusis for all levels of myopia. Issue 1 (16th December 2005) - O'Doherty, M; O'Keeffe, M; Kelleher, C
Abstract : Aims: To assess the long term refractive and visual outcome of patients who have laser in situ keratomileusis (LASIK) surgery. Methods: This was a retrospective study of visual and refractive outcome of patients who had LASIK surgery performed in 1998 and 1999. All levels of myopia were included in the study. 49 patients attended for follow up. The main outcome measures were safety, predictability, efficacy, and stability. Postoperative complications and aberrations were also recorded. The mean preoperative spherical equivalent was −4.85. Results: At 2 months postoperatively 67% of eyes were within plus or minus 0.5D of attempted correction with 81% within plus or minus 1.0D. At 5 years postoperatively 60% of eyes were within plus or minus 0.5D of attempted correction with 83% within plus or minus 1.0D. 88% of eyes had a vision of 6/12 or better at 2 months compared to 89% of eyes at 5 years. Best spectacle corrected visual acuity (BSCVA) was unchanged or improved in 51%. No eye lost more than one line of BSCVA. Overall, there was regression towards myopia with a mean change in refraction of −0.5D over the 5 years. As expected, severely myopic patients regressed more with a mean change of −1.06D. However, there was a high level of patient satisfaction with the surgery. Conclusion: LASIK surgery offers predictable results in terms of refractive and visual outcome with mild regression in refraction over time.